2018
DOI: 10.1016/j.forsciint.2018.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the extent of vertical and lateral movement of human decomposition products through sediment using cholesterol as a biomarker

Abstract: Due to the lack of human decomposition research facilities available in different geographical regions, the extent of movement of human decomposition products from a cadaver into various sedimentary environments, in different climates, has not been able to be studied in detail. In our study, a human cadaver was placed on the surface of a designated plot at the Australian Facility for Taphonomic Experimental Research (AFTER), the only human decomposition facility in Australia, where the natural process of decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…In situations of the discovery of scattered bones, identification of the CDI is key to determining PMI. The spread of CDI can be quite large [30], especially for organic C and N compounds [8], and generally a quick field indication is an increase in soil electrical conductivity where it can be an order of magnitude higher relative to surrounding control soils [17][18]. Body burn (blackening) on the soil surface is also a good indicator of the location of a CDI, which can persist for over one year at some sites or lush vegetation patches which are observable after 18 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situations of the discovery of scattered bones, identification of the CDI is key to determining PMI. The spread of CDI can be quite large [30], especially for organic C and N compounds [8], and generally a quick field indication is an increase in soil electrical conductivity where it can be an order of magnitude higher relative to surrounding control soils [17][18]. Body burn (blackening) on the soil surface is also a good indicator of the location of a CDI, which can persist for over one year at some sites or lush vegetation patches which are observable after 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…At facilities with little slope such as FACTS, expectations are that decomposition products may migrate vertically down the soil profile suggesting the need for deeper samples. Luong et al[30] observed decom-…”
mentioning
confidence: 99%
“…The scope of this research necessarily includes many sciences related to forensic science, such as geology and geophysics, archaeology, environmental science, ecology, botany, pathology and medicine, and analytical chemistry, for example. Current research at AFTER is monitoring how facial tissue thicknesses change with post-mortem interval (Stuzner, 2016), as well as volatile organic compound release from cadavers (Luong et al, 2018;Knobel et al, 2018). In addition, research has also started on the detection of clandestine and mass graves through the use of LiDAR scanning, hyperspectral imagery, infra-red photography and drone imaging (Blau, 2017).…”
Section: Human Conditionsmentioning
confidence: 99%
“…Además la localización e identificación de entierros o sitios que fueron depositarios de inhumaciones, en la actualidad se pueden caracterizar y detectar por medio de la elaboración de un perfil de lixiviación, respecto a la distribución horizontal y vertical del colesterol, en el sustrato circundante al cuerpo enterrado, mediante su persistencia en el ambiente, dado su carácter de biomarcador [53].…”
Section: Exploración Y Prospección De Cementerios Y Tumbas Clandestinasunclassified